Effectiveness of Android-based learning in Physical Education: A literature review study - Al Fatah, M. Agung; Apriani, Leni (Indonesian Journal of Sport Management, 2025)
This literature review aims to review the scientific literature on the effectiveness of android-based learning research in physical education. Two databases (Google Scholar) were used to select articles on the effectiveness of Android-based learning in physical education. After the exclusion criteria, only 11 articles were categorized. The results show the types of research used: qualitative, quantitative, and development. Almost all studies used questionnaires and interviews in data collection. Research on the effectiveness of android-based learning in physical education is divided into two groups: (i) the effectiveness of android-based learning in physical education and (ii) online learning. Several limitations inherent in the review have been noted. First, despite a thorough literature search, some published studies may have been overlooked because the keywords may differ from those currently used. Second, the database (Google Scholar) was used to search for articles. Third, the search for articles from more than one country, namely Indonesia and England.